Teacher candidates’ state of using digital educational games - Ayşe Alkan; Hüseyin Mertol (Institute of Advanced Engineering and Science, 2019)
The rapidly developing information technologies of our age offer new opportunities in every aspect of our lives. The use of information technologies in educational environments is an important element in creating enriched learning environments. Educational digital games used in teaching-learning environments help students to develop motivation, problem-solving, strategy development skills and creativity. The purpose of this research was to determine the teacher candidates’ state of using digital educational games. The study group of the research consisted of 4th-grade teacher candidates who are studying in the social sciences and classroom teaching departments of Süleyman Demirel University during the 2018/2019 academic year. It has been found that men teacher candidates were more positive than women teacher candidates. Teacher candidates studying social sciences were more positive than those studying classroom teaching. Although teacher candidates were concerned about using educational digital games, they were eager to use these games.